2019
DOI: 10.1016/s2214-109x(19)30075-0
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted intervention to improve syphilis screening and treatment in pregnant women in Kinshasa, Democratic Republic of the Congo and in Lusaka, Zambia: a cluster randomised controlled trial

Abstract: Summary Background Despite international recommendations, coverage of syphilis testing in pregnant women and treatment of those found seropositive remains limited in sub-Saharan Africa. We assessed whether combining the provision of supplies with a behavioural intervention was more effective than providing supplies only, to improve syphilis screening and treatment during antenatal care. Methods In this 18-month, cluster randomised controlled trial, we rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 21 publications
(36 reference statements)
3
27
0
1
Order By: Relevance
“…The study also highlighted the need for addressing contradictions in the DRC's national guidelines regarding the place of availability of essential drugs and enhancing the availability of supplies and their utilization. In a recently published cluster randomized controlled trial in Kinshasa and Lusaka (Zambia), Althabe et al showed that a combination of provision of supplies with a behavioral intervention including supportive supervision, the use of opinion leaders, reminders, audit, and feedback, improved the diagnosis and management of maternal conditions such as syphilis [59]. A similar approach could be implemented to improve the quality of care for pre-eclampsia in Kinshasa.…”
Section: Discussionmentioning
confidence: 99%
“…The study also highlighted the need for addressing contradictions in the DRC's national guidelines regarding the place of availability of essential drugs and enhancing the availability of supplies and their utilization. In a recently published cluster randomized controlled trial in Kinshasa and Lusaka (Zambia), Althabe et al showed that a combination of provision of supplies with a behavioral intervention including supportive supervision, the use of opinion leaders, reminders, audit, and feedback, improved the diagnosis and management of maternal conditions such as syphilis [59]. A similar approach could be implemented to improve the quality of care for pre-eclampsia in Kinshasa.…”
Section: Discussionmentioning
confidence: 99%
“…In-country champions could also be utilized to provide encouragement and support as well as mentorship. Previous research has demonstrated the importance of ongoing dissemination of the findings to various actors in different levels of the health care system in order to ensure and maintain stakeholder buy-in for health programs in rural cities [21].…”
Section: Discussionmentioning
confidence: 99%
“…While the ESM-UBT device is both low cost and efficacious [13][14][15], changing health care provider behavior can be complex and challenging [16][17][18][19][20]. There is, however, a growing body of literature that seeks to identify implementation approaches that drive optimal provider performance and quality overall care [16,[18][19][20][21][22]. Tailoring interventions to address known determinants of practice has been shown to influence health care provider practice [23][24][25][26] and a number of authors have emphasized the importance of identifying barriers in order to strengthen implementation efforts [16,17,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…We encourage countries to improve ANC syphilis screening and treatment coverage and to prioritize the use of the UNAIDS GAM system to capture and monitor progress towards EMTCT [7]. Information on the downstream effects of missed opportunities to screen and treat women for syphilis during ANC provide a rich source of evidence for scale up [23,24].…”
Section: Countdown Coveragementioning
confidence: 99%